Thyroid Status, Growth And Development Of Children Under 2 Years Of Age In Endemic Goiter Areas Of Srumbung Magelang - Noor, Zulkhah; Susyanto, Bambang Edi; Praningwestri, Anindhita Mega; Rafiq, Aspar; Havis, Fajar Avivul; Soejono, Sri Kadarsih (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2019)
Objective. To examine the relationship of Iodine urine, TSH and free T4 levels with the growth and development of children under 2 years of age in endemic areas of IDD in Srumbung District, MagelangSubjects. Respondents of this study were 43 respondents mother and her child under 2 years of age who are still breastfeeding. The study was conducted in March until June 2013.Method: observational and cross-sectional data retrieved. Mother urine iodine levels were measured in the laboratory GAKI Borobudur Magelang Indonesia. Levels of serum TSH and free T4 were measured by ELISA in the Clinical Laboratory AMC Yogyakarta with TSH ELISA reagents AIM and AIM fT4 ELISA TESTTEST (PT Intan Accurate Madya). Physical growth include weight, height, head circumference, and upper arm circumference. Weight measured in kilograms (kg), followed by calculation of BMI. Upper arm circumference were measured using standard Wolanski. Child development assessment performed using DDST-II (Denver Development Screening Test II). Data were analyzed with the Pearson correlation test for normal data and Spearman correlation for the data is not normal.Result. Ngargosoko Srumbung Magelang currently have adequate iodine intake with a median urinary iodine concentration of 296 ug / dL, mean blood levels of TSH and fT4 respectively is 1.7187 μIU / mL and 0.8545 ng / dL. But still obtained at 50.84% of respondents hypothyroidism.Conclutions.  Free thyroxine blood levels determine body weight, body length and arm circumference, but did not determine the amount of head circumference, body mass index, the development of gross motor, fine motor, language and personal social. Child development needs to be measured with a measuring device better example with the Bayley Scale of Infant Development (BSID).